A Genome-Wide Association Study of Coleoptile Length in Different Chinese Wheat Landraces - Jun Ma; Yu Lin; Si Tang; Shuonan Duan; Qing Wang; Fangkun Wu; Caixia Li; Xiaojun Jiang; Kunyu Zhou; Yaxi Liu; Yaxi Liu (Frontiers in Plant Science, 2020)
From the perspective of wheat yield improvement, the coleoptile is vital for successful crop establishment, and long coleoptile lengths (CLs) are preferred in wheat-growing regions where deep planting is practiced. To determine the genetic basis of CL, we performed a genome-wide association study on a set of 707 Chinese wheat landraces using 18,594 single-nucleotide polymorphisms and 38,678 diversity array technology sequencing markers. We accordingly detected a total of 29 significant markers [−log10(P) > 4.76] distributed on chromosomes 2B, 2D, 3A, 4A, 5A, 6A, 6B, 6D, and 7B. Based on linkage disequilibrium decay distance, we identified a total of 17 quantitative trait loci associated with CL, among which QCl.sicau-6B.2, located at 508.17–509.26 Mb on chromosome 6B, was recognized as a novel major locus. We subsequently developed a high-resolution melt marker for QCl.sicau-6B.2, which was validated in an F2:3 population. Our findings provide important insights into the genetic mechanisms underlying coleoptile growth and could be applied to marker-assisted wheat selection.